The ecological conscious consumer behaviour: are the activists different?. (27th November 2016) - Brochado, Ana; Teiga, Nídia; Oliveira‐Brochado, Fernando
Abstract: In recent decades, concern about the environment has been increasing. Many individuals are now more worried about their purchasing behaviour and the consequences their actions could have for the environment. Managers are becoming more committed to responding to individual needs and desires in a responsible way, taking into account possible environmental damage. Previous studies concentrated more on explaining this phenomenon through demographic variables, but the trend now is towards explaining this through psychographic and environmental variables, which have already been shown to be the most significant in this context. This study sought to establish the relationship between activists and ecologically conscious consumer behaviour (ECCB) by analyzing the profile of green consumers (i.e. demographic and psychographic variables). To reach this objective, an online survey was conducted. The results of data analyses support the conclusion that activism is the strongest predictor of ECCB.